Liberal versus restrictive red blood cell transfusion strategy in acute coronary syndrome and anemia: an updated systematic review and meta-analysis - Hidri, Sinda; Ur Rehman, Wajeeh; Gardezi, Karam; Shah, Jassim Zaheen; Masetti, Sai Venkata Siddhartha; Almansouri, Naiela E.; Maan, Arslan; Dave, Tirth; Catic, Sumeja; Nagoke, Simranjeet Singh; Rehman, Mohammad Ebad Ur; Cheema, Huzaifa Ahmad; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundIt is uncertain whether a liberal red blood cell (RBC) transfusion strategy is superior to a restrictive approach in patients with acute coronary syndrome (ACS) and anemia.MethodsWe searched MEDLINE, Embase, the Cochrane Library, and ClinicalTrials.gov from inception to April 2024 for randomized controlled trials (RCTs) comparing liberal and restrictive transfusion strategies in ACS patients with concurrent anemia.ResultsFive RCTs (4,510 patients) were included in this meta-analysis. There was no significant difference between the liberal and restrictive RBC transfusion strategy groups in the risk of major adverse cardiovascular events (MACE) (RR 0.91, 95% CI: 0.68–1.21; I2 = 63%) and all-cause mortality (RR 0.85, 95% CI: 0.72, 1.00; I2 = 0%). A liberal transfusion strategy reduced the risk of myocardial infarction (MI) (RR 0.80, 95% CI: 0.66, 0.98; I2 = 0%). There were no significant differences between the two strategies in the risk of revascularization, heart failure, stroke, cardiac mortality, acute kidney injury or failure, and pneumonia, bacteremia, or infection. Liberal transfusion increased the risk of acute lung injury (RR 8.97, 95% CI: 1.65, 48.65; I2 = 0%).ConclusionsOur meta-analysis demonstrated that a liberal RBC transfusion strategy reduced the risk of MI and increased the risk of acute lung injury but did not affect other clinical outcomes compared to a restrictive approach in patients with mainly acute MI and anemia. New large-scale multicenter RCTs are required to confirm or refute our findings and provide more reliable results.Systematic Review RegistrationPROSPERO (CRD42024506844).